Survey of Student Interest Madrasah Aliyah Nurul Islam Ngemplak towards Football Sports - Rizky Sangidal Mubarok; Eko Sudarmanto (UNIB Press, 2023)
Ngemplak Islam is favored by students, this is influenced by the response from students and schools. The purpose of this study was to determine the interest of Madrasah Aliyah Nurul Islam Ngemplak students in the sport of football and the benefits of football sports. The samples in this study were class X, XI, and XII students totaling 57 students of Madrasah Aliyah Nurul Islam Ngemplak. The results of this study stated that the interest of Madrasah Aliyah Nurul Islam Ngemplak students in the sport of football is very large. It is proven that 88% of Madrasah Aliyah Nurul Islam students have an interest in the sport of football. There are several indicators of why Madrasah Aliyah Nurul Islam Ngemplak students like the sport of football, namely: the body becomes healthy and fit, refreshes the brain, and wants to excel in the sport of football. In addition, many students of Madrasah Aliyah Nurul Islam Ngemplak want to become football athletes, they also want to be committed to the sport of football, so that their desire to become football athletes can be achieved.